2021
DOI: 10.1177/15248399211014490
|View full text |Cite
|
Sign up to set email alerts
|

Digital Disenfranchisement and COVID-19: Broadband Internet Access as a Social Determinant of Health

Abstract: According to the Pew Research Center, approximately one quarter of American adults do not have access to broadband internet. This number does not account for the millions of people who are underconnected or lacking a stable internet connection. Although digital disparity in America is not new, the COVID-19 (coronavirus disease 2019) pandemic has increased our societal dependence on the internet and widened the digital divide. Access to broadband internet has become a basic need in this connected society, linki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 4 publications
0
59
0
Order By: Relevance
“…The impact of territorial digital inequality in Internet use on the spread of COVID-19 in the EU reflects the presence of challenges regarding the accessibility of the Internet in remote areas [12,13]. The presence of regional digital differences has already had a negative effect on the increase in the number of cases of COVID-19 between the first and second waves of the pandemic in 2020.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of territorial digital inequality in Internet use on the spread of COVID-19 in the EU reflects the presence of challenges regarding the accessibility of the Internet in remote areas [12,13]. The presence of regional digital differences has already had a negative effect on the increase in the number of cases of COVID-19 between the first and second waves of the pandemic in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…While the digital disparity in the US is not new, the COVID-19 pandemic has increased societal dependence on the Internet and widened the digital divide. People's reliance on the Internet for access to everything from work and online school to telemedicine and food leads to the fact that, from a social point of view, broadband Internet should be seen as a basic need, not a privilege [12]. A study examining areas in Poland that are particularly vulnerable to digital deprivation due to infrastructure deficiencies during the pandemic indicated that 4% of Poles remain without Internet access, and the access of an additional 10% is too slow to allow effective remote work or learning [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“… 145 However, it also widened the access gap among children and families with limited access to internet and personal electronic devices. 146 Increasing families’ access to technology and in particular internet services may prove a potent public health intervention. Of course, in person child health visits remain critically important for child health.…”
Section: Creating An Equitable and Just Recovery For Children And Youthmentioning
confidence: 99%
“…Remote and rural areas are underserved and have poorer quality connections to the internet (Aissaoui 2021, Riddlesden, Singleton 2014, Tranos, Mack 2016. For example, in the US, less than half of indigenous people residing on reservations and tribal lands have access to high speed broadband due to providers' reluctance to build ICT infrastructure in less populated areas (Early, Hernandez 2021). Bosworth et al (2020) argue that a spatially uneven ICT infrastructure leads to inequalities in digital skills and an inability to attract digitally skilled workers or firms to rural areas.…”
Section: Urban Vs Ruralmentioning
confidence: 99%